Price convergence in the enlarged internal market - Christian Dreger; Konstantin Kholodilin; Kirsten Lommatzsch; Jirka Slacalek; Przemyslaw Wozniak (Center for Social and Economic Research (CASE), 2007)
In this paper we investigate the effects of EU enlargement on price convergence. The internal market is expected to boost integration and increase efficiency and welfare through a convergence of prices in product markets. Two principal drivers are crucial to explain price developments. On the one hand, higher competition exerts a downward pressure on prices because of lower mark ups. On the other hand, the catching up process of low income countries leads to a rise in the price levels and higher inflation over a transition period. Using comparative price levels for individual product categories price convergence can be established. However, the speed of convergence is rather slow, with half lives around 10 years. The enlargement has slightly stimulated the convergence process, and this impact is robust across different groups of countries. Moreover, the driving forces of convergence are explored. In line with theoretical predictions, the rise in competition exerts a downward pressure on prices, Chile catching up of low income countries leads to a rise in price levels.
Keywords: E31; F15; C33; 330; EU enlargement; price convergence; catching up and competition; Inflationsrate; Inflationskonvergenz; Preiskonvergenz; EU-Binnenmarkt; EU-Mitgliedschaft; EU-Staaten; EU-Mitgliedschaft